Inter-Organizational Networks in Politics: A Case Study of the National Democratic Alliance in India - Rashmi; Nijhawan, Garima (Prabandhan: Indian Journal of Management, 2015)
Inter-organizational networks have a wide-ranging presence in fields as diverse as sociology, mergers&acquisitions, business management, political science, and public administration. Inter-organizational networks are especially important for strategic alliances. The present study is an illustration of such networks. It developed an understanding of inter-organizational dynamics through a case-study of NDA, a major political alliance in India.